Transparent and Accountable Governance of State Civil Servants (ASN) Position Transfers and Promotions: A Qualitative Study in the Field of Formation and Transfers Regional Personnel Agency of Pasuruan City - Braja Manastha Winduaji; Fedianty Augustinah; Eny Haryati (International Journal of Humanities and Social Sciences Reviews, 2025)
This research seeks to examine the management of transparent and accountable civil service transfers and promotions in the Formation and Mutation Division of Pasuruan City's Civil Service Agency (BKD). The study is based on the significance of the merit system in upholding bureaucratic professionalism, since the procedures for transfer and promotion frequently influence equity and organizational effectiveness. Employing a qualitative case study method, data were gathered via in-depth interviews, participatory observations, and document examination. The results show that the transfer and promotion systems in BKD Pasuruan have progressed towards transparency via data-driven management, yet obstacles persist in communicating policies and involving employees in performance evaluations. Accountability has been enhanced via performance-driven assessments incorporated with the e-performance system and job analysis. The conversation emphasizes that the effectiveness of governance practices is affected by organizational flexibility, engaged leadership, and the public service motivation of civil servants. This research determines that the interplay of data-based policies, performance assessment frameworks, and a transparent bureaucratic environment establishes the basis for creating a just, efficient, and sustainable civil service governance model.